A Municipal Register of the City of Concord, Containing the City Charter and Ordinances, the Rules of the City Council, and a List of the City Officers Page 74, Image 75 (1868) § 1 - (:unkn) unknown (General Publisher, 1868)
No person shall discharge any gun or fire-arms within, on, or at, any bridge or building belonging to the city, or in any way damage the same, or any fence or other property belonging to the city, or write upon, cut out, or make any obscene image or representation
--
Keywords: DISCHARGE